Validation of the Writing Strategies Questionnaire in the Context of Primary Education: A Multidimensional Measurement Model - Arias-Gundín, Olga; Real, Sara; Rijlaarsdam, Gert; López, Paula (Frontiers in Psychology, 2021)
Research has shown that writers seem to follow different writing strategies to juggle the high cognitive demands of writing. The use of writing strategies seems to be an important cognitive writing-related variable which has an influence on students’ writing behavior during writing and, therefore, on the quality of their compositions. Several studies have tried to assess students' writing preferences towards the use of different writing strategies in university or high-school students, while research in primary education is practically nonexistent. The present study, therefore, focused on the validation of the Spanish Writing Strategies Questionnaire (WSQ-SP), aimed to measure upper-primary students’ preference for the use of different writing strategies, through a multidimensional model. The sample comprised 651 Spanish upper-primary students. Questionnaire data was explored by means of exploratory (EFA) and confirmatory (CFA) factor analysis. Through exploratory factor analysis four factors were identified, labelled thinking, planning, revising and monitoring, which represent different writing strategies. The confirmatory factor analysis confirmed the adequacy of the four-factor model, with a sustainable model composed of the four factors originally identified. Based on the analysis, the final questionnaire was composed of 16 items. According to the results, the Spanish version of the Writing Strategies Questionnaire (WSQ-SP) for upper-primary students has been shown to be a valid and reliable instrument, which can be easily applied in the educational context to explore upper-primary students’ writing strategies.